Essential role of DNA-PKcs and plasminogen for the development of doxorubicin-induced glomerular injury in mice - Bernhard N. Bohnert; Irene Gonzalez-Menendez; Thomas Dörffel; Jonas C. Schneider; Mengyun Xiao; Andrea Janessa; M. Zaher Kalo; Birgit Fehrenbacher; Martin Schaller; Nicolas Casadei; Kerstin Amann; Christoph Daniel; et al. (The Company of Biologists, 2021)
Susceptibility to doxorubicin-induced nephropathy (DIN), a toxic model for the induction of proteinuria in mice, is related to the single-nucleotide polymorphism (SNP) C6418T of the Prkdc gene encoding for the DNA-repair enzyme DNA-PKcs. In addition, plasminogen (Plg) has been reported to play a role in glomerular damage. Here, we investigated the interdependence of both factors for the development of DIN. Genotyping confirmed the SNP of the Prkdc gene in C57BL/6 (PrkdcC6418/C6418) and 129S1/SvImJ (PrkdcT6418/T6418) mice. Intercross of heterozygous 129SB6F1 mice led to 129SB6F2 hybrids with Mendelian inheritance of the SNP. After doxorubicin injection, only homozygous F2 mice with PrkdcT6418/T6418 developed proteinuria. Genetic deficiency of Plg (Plg−/−) in otherwise susceptible 129S1/SvImJ mice led to resistance to DIN. Immunohistochemistry revealed glomerular binding of Plg in Plg+/+ mice after doxorubicin injection involving histone H2B as Plg receptor. In doxorubicin-resistant C57BL/6 mice, Plg binding was absent. In conclusion, susceptibility to DIN in 129S1/SvImJ mice is determined by a hierarchical two-hit process requiring the C6418T SNP in the Prkdc gene and subsequent glomerular binding of Plg. This article has an associated First Person interview with the first author of the paper.